2021
DOI: 10.1021/acsfoodscitech.1c00019
|View full text |Cite
|
Sign up to set email alerts
|

Fighting the COVID-19 Pandemic through Biofortification: Innovative Approaches to Improve the Immunomodulating Capacity of Foods

Abstract: Nutrients such as vitamins C and D and selenium have potential for the reduction of risk and amelioration of COVID-19 disease. Although different foods contain these nutrients, their natural concentration is not sufficient to provide the required daily intake to exert immunomodulating activity. Herein, innovative approaches, including pre-and postharvest practices for the biofortification of foods (i.e., eggs, tomato, acerola, mushrooms, wheat, and chickpea) with immunomodulating nutrients are described. Enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
(108 reference statements)
0
8
0
Order By: Relevance
“…Therefore, to meet the recommended daily intakes, supplementation of vitamins and minerals is needed [65]. Fortification of foods has gained relevance in the last year, since it has been demonstrated that low blood levels of vitamins C and D, zinc, and selenium correlates with the development of severe cases of COVID-19 disease [66]. Also, the deficiency of minerals such as iron is a frequent nutritional problem around with a significant impact on growth as well as on intellectual and psychomotor development in children.…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
“…Therefore, to meet the recommended daily intakes, supplementation of vitamins and minerals is needed [65]. Fortification of foods has gained relevance in the last year, since it has been demonstrated that low blood levels of vitamins C and D, zinc, and selenium correlates with the development of severe cases of COVID-19 disease [66]. Also, the deficiency of minerals such as iron is a frequent nutritional problem around with a significant impact on growth as well as on intellectual and psychomotor development in children.…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
“…Agronomic biofortification success stories have been reported using Se-fertilization in Finland, Zn-fertilization in Turkey, and iodine-fertilization in China, among many others. Biofortification, in turn, can increase human resistance to diseases such as COVID-19, thus helping combat the current epidemic (73).…”
Section: Biofortification For Human Healthmentioning
confidence: 99%
“…Improving human health may include providing people with enough safe nutrients to avoid malnutrition and allow the immune system to fight against multiple diseases such as COVID-19 (73,79). The COVID-19 pandemic has a strong relationship with other outbreaks such as severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS).…”
Section: Soil Health Biofortification and Covid-19mentioning
confidence: 99%
“…Given the positive impact of this micronutrient resistance on human immune function, it is also likely to increase people's resistance to potential future pandemics. Gastélum-Estrada et al (2021) reported that consumption of biofortified foods (tomato, acerola, mushrooms, wheat, chickpea, etc. ) in addition to vaccination would strengthen the immune system and suggested it as a realistic approach that could help reduce the risk of COVID-19 disease.…”
Section: Introductionmentioning
confidence: 99%